Helicobacter pylori eradication by low‐dose rifabutin triple therapy (RHB‐105) is unaffected by high body mass index. Issue 7 (17th November 2021) - Kao, John Y.; Almenoff, June S.; Portenier, Dana D.; Sheldon, Kely L.
Abstract: Background: Helicobacter pylori infection affects 35% of Americans and may lead to serious sequelae if left untreated, including gastric cancer. Obesity is a significant risk factor for antibiotic treatment failure; however, little work has been done to understand the influence of high body mass index (BMI) on the success rates of H pylori eradication regimens in treatment‐naïve and refractory adult patients. Aim: This analysis evaluated the association of subject obesity on overall H pylori eradication rates for RHB‐105 (rifabutin, amoxicillin, and omeprazole magnesium; Talicia ® ) and its comparators using data from two Phase 3 clinical trials. Methods: A post hoc analysis of the eradication rates of RHB‐105 vs comparators in a total of 269 subjects who tested positive for H pylori was conducted. Comparators in the two studies included placebo (placebo comparator) and amoxicillin and omeprazole (active comparator). Subjects were treated for 14 days and returned for follow‐up test‐of‐cure at 28‐59 days post‐therapy using urea breath testing. Results: Subjects receiving RHB‐105 with 30 ≤ BMI < 40 or BMI ≥ 40 had pooled modified intent to treat (mITT) eradication rates of 88.1% (95% CI: 81.1‐92.8) and 90.9% (95% CI: 72.2‐97.5) [ P = .707], respectively, compared to active comparator rates of 62.9% (95% CI: 52.5‐72.2) and 31.8% (95% CI: 16.4‐52.7) [ P = .008]. Conclusions: Obese patients treated with RHB‐105 were associated with efficacy rates comparable to the overall study population. This supports further evaluation of the efficacy of RHB‐105 in obese populations, where H pylori is prevalent. ClinTrials.gov # NCT01980095 & NCT031985070.